COLLABORATIVE GOVERNANCE IN WASTE MANAGEMENT (Study In The Integrated Waste Management Site Of Tambakrejo Area, Sidoarjo Regency) - Adelia Dwinta Amelinda; Arimurti Kriswibowo (DIA: Jurnal Administrasi Publik, 2021)
Sidoarjo Regency as one of the districts in East Java faces problems in waste management.  Currently, Sidoarjo Regency has a high population density and has become an industrial area.  This has in increasing the number of waste piles. To reduce the amount of waste pile at the TPA and the source, the government has built an Integrated Waste Management Site  (TPST). This study aims to determine how the collaborative process between the government,  the public, and the private sector is taking place in the TPST Tambakrejo area. The type of research used in this article is to use a qualitative approach. The results showed that the collaboration process at the TPST Tambakrejo area was up and running even though there were still obstacles. This research concludes that’s collaborative governance has been running optimally. This can be seen from the collaboration aspects of Ansell and Gash